Vegetative growth and leaf greenness of oil palm seedlings as affected by chicken manure and compost in Ultisol subsoil media - Dimas Prakoswo Widiyani; Bela Ayu Pratiwi; Tyas Dwi Chintya; Husna Husna; AH Maftuh Hafidh Zuhdi; Anggia Fanesa; Abdul Aziz; Lely Juli Anti Siregar (Agrovigor, 2026)
Oil palm seedling growth is highly affected by the planting media. The planting media commonly used in oil palm nurseries are derived from subsoil, which has low fertility levels and therefore requires improvement through the addition of organic fertilizers. The application of compost and chicken manure has been shown to enhance the growth of oil palm plants by increasing macro and micronutrient availability, improving organic matter content, enhancing soil structure, and supporting microbial activity. This study aimed to determine the optimal planting medium combination for the growth of oil palm seedlings during the main nursery stage. The experiment was arranged in a Randomized Complete Block Design (RCBD) with five treatments, namely: P0 = control (subsoil), P1 = 2:1 (subsoil + compost), P2 = 1:1 (subsoil + compost), P3 = 2:1 (subsoil + chicken manure), and P4 = 1:1 (subsoil + chicken manure). Each treatment was replicated four times, and the observed parameters included plant height, number of leaves, stem diameter, leaf greenness, and c-organic. The observed data were analyzed using an F-test, followed by a Least Significant Difference (LSD) test at the 5% significance level. The results showed that the addition of compost or chicken manure to the subsoil planting medium improved the growth of oil palm seedlings at the main nursery stage. The P4 treatment (subsoil + chicken manure at a 1:1 ratio) significantly improved plant height, number of leaves, stem diameter, and leaf greenness of oil palm seedlings, and produced the highest organic carbon content among treatments.